Problems of Regional Industrial Projects Realization - SHALDARBEKOV, Kairat B.; MUKHANOVA, Gulmira S.; DOSSOVA, Senymgul N.; MUSSAEVA, Gulnar K.; NURMUKHAMBETOVA, Zaure S.; SHALDARBEKOVA, Karlygash B. (Journal of Advanced Research in Law and Economics, 2019)
The article studies the problems of implementing regional industrial projects. The authors conducted a literature review and identified modern trends in project management at the regional level. To identify the problems of implementing regional projects, a sociological study was conducted using the questionnaire method. As respondents, the managers and customers of the projects were selected. 39 respondents took part in the survey. Based on the results of the study, the main problems encountered in the implementation of regional projects were identified, as well as the factors for their successful implementation.